2013
DOI: 10.1007/s12288-013-0294-8
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of 1q21 and Other Abnormalities in Multiple Myeloma Patients from a Tertiary Hospital in Singapore

Abstract: Much effort has been made to stratify multiple myeloma patients for targeted therapy. However, responses have been varied and improved patient stratifications are needed. Forty-five diagnostic samples from multiple myeloma patients (median age 65 years) were stratified cytogenetically as 15 having non-hyperdiploidy, 20 having hyperdiploidy and 10 having a normal karyotype. Fluorescence in situ hybridization (FISH) assays with FGFR3/IGH, CCND1/IGH, IGH/MAF, RB1 and TP53 probes on bone marrow samples showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
4
0
2
Order By: Relevance
“…In our study, 14q32 amplification/deletion was observed in 72.7% of patients, and t(4;14) was the most common aberration. Lim et al 4 reported that IGH rearrangements were the most common abnormality. t(4p16.3/14q32) rearrangements were most frequent.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 14q32 amplification/deletion was observed in 72.7% of patients, and t(4;14) was the most common aberration. Lim et al 4 reported that IGH rearrangements were the most common abnormality. t(4p16.3/14q32) rearrangements were most frequent.…”
Section: Discussionmentioning
confidence: 99%
“…1q21 gain is one of the most common chromosomal aberrations in MM, especially in nonwhite patients . 1q21 gain is detected in 30% to 50% of patients with NDMM .…”
Section: Introductionmentioning
confidence: 99%
“…The patients can be roughly divided into two categories according to chromosomal structure and numerical abnormalities: hyperdiploid and non‐hyperdiploid. 12 Odd chromosome trisomy usually occurs in hyperdiploids, mainly including +3, +5, +7, +9, +11, +15, +19, and +21. 13 Non‐hyperdiploid genes are often associated with translocations between IgH genes and other chromosomes.…”
Section: The Pathogenesis Of MMmentioning
confidence: 99%
“…Cytogenetic abnormality is one of the main basis for risk stratification of MM. The patients can be roughly divided into two categories according to chromosomal structure and numerical abnormalities: hyperdiploid and non‐hyperdiploid 12 . Odd chromosome trisomy usually occurs in hyperdiploids, mainly including +3, +5, +7, +9, +11, +15, +19, and +21 13 .…”
Section: The Pathogenesis Of MMmentioning
confidence: 99%